Synthesis and characterizations of a novel trans-Pd(O,N)2 complex with an AZO-dye ligand: Crystal structure, theoretical studies and DNA binding interactions - Souheyla Chetioui; Zineb Fellahi; Amel Djedouani; Jean-Pierre Djukic; Abeer A. AlObaid; Khalil Shalalin; Anas AlAli; Nidal Jaradat; Ismail Warad (Scientific African)
The transition metal-azo dye complexes have attracted attention in both fundamental and applied research due to their electronic and structural properties, particularly due to their potential to yield new compounds with diverse biological activities and anticancer agents. A novel square planar-trans-Pd(O,N)2 was synthesized with a high yield utilizing a one-pot approach employing (E)-methyl 2-((2-hydroxynaphthalen-1-yl)diazenyl)benzoate as the AZO-dye ligand. In order to analyze their structure and understand their properties. The desired complex was characterized using FT-IR, UV–Vis, NMR, and CHN-EA techniques. Subsequently, theoretical modeling of the complex was performed using MEP/MAC/NPA methodologies. Two methodologies were employed to monitor the coordination process of AZO-ligand with Pd(II): UV–Vis absorption and FT-IR spectrum analysis. The TD-DFT and DFT/IR behaviors were simultaneously assessed to compare the experimental results with theoretical predictions. Furthermore, both SC-XRD and DFT analysis demonstrated that the deprotonated phenolic diazene form of the AZO-ligand attached to the Pd(II) center by utilizing one nitrogen atom of the AZO-ligand and the ionic oxygen of the phenol. The SC-XRD analysis verified the presence of a slightly distorted square-planar geometry around the PdII center in the neutral trans-Pd(O,N)2 complex. All of the oxygen atoms in the complex participated in non-classical C-H….O hydrogen bonding, leading to the formation of novel edge-fused rings R22(24) and R22(12) synthons. These synthons create a 3D-network with a linked parallel matrix. Interestingly, Hirshfeld surface analysis (HSA) stimulation revealed many hot sites on the complex surface, confirming the formation of strong non-classical [C-H....O] interactions. From the observed docking behavior with the DNA, it can be concluded that the trans-Pd(O,N)2 showed superior binding compared to the free AZO-ligand. The results of this work are a contribution to the study of this class of metal complexes and their physicochemical properties and offer promising perspectives for the realization of new works.